ЛИЗИНГОВЫЙ МЕХАНИЗМ В РАЗВИТИИ ЭКОНОМИКИ (Journal of Economic Research & Business Administration, 2015)
Market economic and financial relations, that are connected with the estimated of leasing potential and its usage, are widely spread on the territory of the RK.